Electronic nose ammonia gas monitoring via IoT system for Chlorella sp. cultivation - Keerayoot Srinuanjan; Aphichaya Kruakuanphet; Phachara Phongwisit; Witoon Yindeesuk; Surachart Kamoldilok (My University, 2023)
In this paper, we present an electronic nose ammonia gas monitoring via IoT system for Chlorella sp. cultivation. The MQ–137 gas sensor module is selected as the primary sensor for measuring ammonia gas concentration. The pH sensor module is the sensor for measuring the pH levels in Chlorella sp. ponds. The MQ–137 gas sensors are calibrated with a known concentration of ammonia gas in the calibration box. Calibration conditions are set corresponding to low concentration of ammonia gas produced by Chlorella sp. cultivation. The pH sensor module is calibrated against a standard pH buffer. The calibration data obtained from the calibration method is input into computer programming and processed by the ESP8266 microprocessor. After calibration, the MQ–137 gas sensor and pH sensor modules are used to measure the ammonia gas concentration and pH levels in the Chlorella sp. ponds. Chlorella sp. is cultivated under three conditions of light intensity, natural light with an average light intensity of 1521 Lux, and artificial light with a light intensity of 1000 Lux and 2000 Lux, respectively. The ammonia gas concentration and pH levels of Chlorella sp. cultivation are transferred to the cloud system and displayed via the IoT system. And the system can also send a notification to a smartphone when ammonia gas concentration and the pH levels reach the specified value.
Keywords: Water Quality Monitoring Technologies; Water Quality Monitoring and Analysis; Analytical Chemistry and Sensors